Incidence of cardiovascular events in HIV-positive patients compared to general population over the last decade: a population-based study from 2000 to 2012. Issue 12 (1st December 2016) - Quiros-Roldan, Eugenia; Raffetti, Elena; Focà, Emanuele; Brianese, Nigritella; Ferraresi, Alice; Paraninfo, Giuseppe; Pezzoli, Maria Chiara; Bonito, Andrea; Magoni, Michele; Scarcella, Carmelo; Castelli, Francesco
ABSTRACT: Cardiovascular diseases are currently a main cause of death among people living with HIV. This population-based study aimed to investigate the incidence of cardiovascular events (CVEs) in HIV-positive people and factors associated with CVEs. We performed a retrospective cohort study of the HIV-infected patients residing in the Local Health Authority of Brescia, northern Italy, from 2000 to 2012. Incidence of CVEs events in HIV-positive patients was compared with that expected in general population living in the same area, computing standardized incidence ratios (SIRs). CVEs-associated risk factors were assessed using Cox regression analysis and competing risk model of death. About 3766 HIV-infected patients were included in the study. Over the 12-year-period, we recorded 134 CVEs: 83 (61.9%) acute myocardial infarctions (CVE type-1), and 51 (38.1%) strokes (CVE type-2). A twofold increased risk (SIR = 2.02) of CVEs was found in HIV-infected patients compared to the general population. Notably, within male patients: for CVE type-1, SIR = 1.89, for CVE type-2 SIR = 2.25; within female patients: for CVE type-1, SIR = 2.91, for CVE type-2 SIR = 2.07. Age >45 years, male gender, diabetes, and total blood cholesterol >200 mg/dl were significantly associated with CVEs incidence (for all, p < .05). These results were confirmed using the competing risk model. Our cohort study confirmed the higher incidence of CVEs in HIV-positive patients, and put emphasis on the importance of traditional cardiovascular risk factors. Overall CVE risk in HIV-positive patients was twice as high as CVE risk in general population. We found a peculiar gender distribution, with a relative risk for CVE type-1 higher in HIV-positive females, and a higher CVE type-2 risk in male patients. More studies are needed in order to support these findings and to further highlight possible gender differences in the risk of developing CVEs in HIV-positive patients.